Framework Administered Account for Selected Fund Activities : Norway Subaccount for Selected Fund Activities. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
The Fund, represented by the Managing Director, has reached understandings with Norway acting through the Ministry of Foreign Affairs ("Norway"), to finance capacity building, training and related activities. On the basis of these understandings, the Managing Director has established the essential terms and conditions of the Subaccount, with which Norway concurs, with respect to the nature, design, and implementation of the activities to be financed and the method by which the costs of the activities will be financed from the Subaccount.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Fund Member; PP; Subaccount; Terms and Conditions Of The Subaccount; Terms and Conditions; Norway